The role of educational robots in developing the programming skills of secondary school students and the obstacles to their use from the point of view of female teachers in Jeddah - Alamri, Wardah Gharman (Journal of Curriculum and Teaching Methodology, 2022)
The current study aimed to reveal the role of educational robots in developing programming skills for secondary school students and the obstacles to their use from the point of view of teachers in Jeddah. The questionnaire was also used to collect the required data, which consisted of (42) phrases in two main axes, after which the data was analyzed by means of a single-sample T-test, and the results showed that the degree of approval of the female teachers who were participants in the study was big, and the obstacles that they might face when they are teaching the programming skills of female students by using educational robots were very large, and in light of this the study recommended the use of robots in teaching programming skills and the need to reduce the obstacles to the use of robots in teaching by teachers.
Keywords: Robots; Programming skills